Pengaruh Program Literasi Terhadap Prestasi Belajar Siswa Kelas III SDN 244 Inpres Bera Kabupaten Tana Toraja - Irene Hendrika Ramopoly; Hasriani Zainuddin (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
Literacy program is a reading activity 15 minutes before the study time begins. Literacy programs teach students the ability to independently access, understand, and use things intelligently through reading, writing, seeing, listening, and speaking activities that can be realized in life. This research aims to find out "The Influence of Literacy Program on The Learning Achievement of Grade III Students of SDN 244 Inpres Bera Kabupaten Tana Toraja". This research is quantitative research. The subjects in this study were grade III students of SDN 244 Inpres Bera Kabupaten Tana Toraja in the 2019/2020 school year which numbered 22 students (1 class).Data collection techniques using Likert Scale and documentation. The scale of the literacy program used in this study uses a questionnaire provided by researchers and has tested the validity of 14 statements, and achievements using the student report value documentation. Data analysis techniques are performed with descriptive statistics. Hypothetical testing uses Product Moment correlation analysis. The results showed a correlation rate of 0.527 indicating the influence of both variables in the moderate category, with a value of 0.012<0.05. Thus H1 is accepted and H0 is rejected meaning that there is an influence of literacy program on the learning achievement of grade III students of SDN 244 Inpres Bera.